2013
DOI: 10.1088/0957-4484/24/43/435702
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure and strain in InGaN/GaN superlattices grown in GaN nanowires

Abstract: The structural properties and the strain state of InGaN/GaN superlattices embedded in GaN nanowires were analyzed as a function of superlattice growth temperature, using complementary transmission electron microscopy techniques supplemented by optical analysis using photoluminescence and spatially resolved microphotoluminescence spectroscopy. A truncated pyramidal shape was observed for the 4 nm thick InGaN inclusions, where their (0001¯) central facet was delimited by six-fold {101¯l} facets towards the m-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 64 publications
4
50
1
Order By: Relevance
“…The film also exhibits a peak at 3.41 eV, which corresponds to underlying GaN layer. A second peak at 2.94 eV might correspond to the thin InGaN strain-relieving layer with~6% of In [62,63]. The indium composition of the InGaN layer was calculated using Vegard's law and was found to be 22% in sample E, which is in correlation with the value as estimated by HRXRD.…”
Section: Polar Ingan/gan Heterostructuressupporting
confidence: 63%
“…The film also exhibits a peak at 3.41 eV, which corresponds to underlying GaN layer. A second peak at 2.94 eV might correspond to the thin InGaN strain-relieving layer with~6% of In [62,63]. The indium composition of the InGaN layer was calculated using Vegard's law and was found to be 22% in sample E, which is in correlation with the value as estimated by HRXRD.…”
Section: Polar Ingan/gan Heterostructuressupporting
confidence: 63%
“…In any case, the bottom-up fabrication of NW based QW structures seems to induce larger inhomogeneities in the alloy composition of the insertions than for planar QWs. Along this line, Kehagias et al [11] have shown that for lower growth temperatures of the (In,Ga)N insertions, the inhomogeneity of the alloy is further increased and the width of the (In,Ga)N band for the NW ensemble can amount to 800 meV. A certain degree of localization might well be necessary to avoid the possibility of detrimental carrier recombination at the NW surface in line with what is discussed for dislocations in planar layers [48].…”
Section: Single Nw Photoluminescencementioning
confidence: 68%
“…From previous studies, it is known that the large FWHM of the (In,Ga)N emission in NW ensembles partly results from a variation in the emission energy between individual NWs [4,7,11,17]. In [17], it is shown that the peak energy of the (In,Ga)N band for single NWs can vary over a range of about 400 meV.…”
Section: Single Nw Cathodoluminescencementioning
confidence: 99%
“…The emission peak at around 3.41 eV is assigned to the emission from the under layer GaN film. The emission peak at around 2.94 eV is assigned to the recombination in the thin GaN under-layer in which a small amount ($6%) of indium atoms incorporate due to the diffusion [12,13]. From the PL peak position the composition of indium in InGaN alloy was calculated using standard bowing equation, given by…”
Section: Resultsmentioning
confidence: 99%